Effects of black pepper, tulsi, peppermint, garlic, black cumin, papaya, cinnamon and patent probiotics on growth performance of broiler - Amin, Mohammad Rohul; Khokon, Md Mehedi Hasan; Akter, Nasrin; Imran, Md Nurul Al; Uddin, Md Jasim; Reza , Md Ahsanur (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The experiment was conducted in Department of Physiology and Pharmacology, FANSVM, PSTU to study the effects of seven indigenous medicinal plants [black pepper (Piper nirgum), tulsi (Ocimum sanctum), peppermint (Mentha piperita), garlic (Allium sativum), black cumin (Nigella sativa), papaya (Carica papaya), cinnamon (Cinnamomum verum)] and two patent probiotics (SS Bio® and Poultrystar Sol®) on the growth performance (body weight and FCR) in broiler. The effects of black pepper, tulsi, peppermint, garlic, black cumin, papaya, cinnamon, SS Bio® and Poultrystar Sol® on hematological parameters (TEC, Hb and PCV) and biochemical parameter (blood glucose) were also observed. One hundred broiler were randomly divided into ten groups (A, B, C, D, E, F, G, H, I and J), each consisting of ten broiler. Group A was kept as control. 10% water extract of black pepper (seed), tulsi (leaves), peppermint (leaves), garlic (bulbs), black cumin (seed), papaya (leaves), cinnamon (bark) were administered orally to the broiler of group B, C, D, E, F, G and H, respectively. Broiler of group I and J received orally SS Bio® and Poultrystar Sol®, respectively. Black pepper, tulsi, peppermint, garlic, black cumin, papaya, cinnamon, SS Bio® and Poultrystar Sol® were significantly (p<0.01 and p<0.05) increased body weight and FCR up to the experimental period. TEC was significantly (p<0.05) increased at garlic treated broiler. After treatment with peppermint, garlic, black cumin, papaya, cinnamon, SS Bio® and Poultrystar Sol®, Hb content increased significantly (p<0.05) in broiler. Black pepper, tulsi, peppermint, black cumin, papaya, SS Bio® and Poultrystar Sol® treatment significantly (p<0.01 and p<0.05) increased PCV in broiler. Peppermint, garlic, black cumin, papaya, cinnamon, SS Bio® and Poultrystar Sol® caused significantly (p<0.01 and p<0.05) increased blood glucose. Tulsi decreased (p<0.05) significantly blood glucose. The present study reveal that indigenous medicinal plants can be used as alternatives to patent probiotics in broiler. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (3), 135-141